Words around information literacy: construction and use of concepts to support scholarship as conversation - Sanches, Tatiana (2022)
Inspired by Scholarship as Conversation, a frame from the conceptual ACRL Framework (ACRL, 2016), this study aims to reflect on Information Literacy concepts, expressed in a specific terminology, that the discipline, particularly in higher education, has been adding, contributing to the construction of this scientific area and dialogue in academy and profession. The work seeks to demonstrate how concepts of information literacy in higher education have evolved in parallel with the publication of theoretical frameworks, defined from guiding documents. This vision aims to clear knowledge of the discourse produced on information literacy, showing trends, and investigative clues. Terminology produced in Information Literacy strengthens the affirmation of the disciplinary field, benefiting the scientific community through a more assertive and understandable dialogue between researchers.